Determination of Agropolitan Areas Based on Leading Commodities of Horticultural Crop Production, Food Crop Production, and its Effect on the GRDP of the Agricultural Sector of Malang Regency - Alamsyah, Rachmad Rifqi; Setiawati, Ririt Iriani Sri (Indonesian Journal of Business Analytics, 2023)
The agricultural sector can play a role in reducing the gap between rural and urban areas which has the effect of hindering the growth and development of economic development in Malang Regency. The purpose of this study is to determine the leading commodities and their influence on agricultural sector GRDP to help increase economic growth. The use of LQ analysis to determine the leading commodities of horticultural crop production and food crop production. Panel data regression analysis to determine the effect of independent variables on agricultural sector GRDP. It is known that there are top base sectors in Poncokusumo and Donomulyo sub-districts. Assessed an insignificant positive effect between horticultural crop production on the dependent variable, while a significant positive effect between food crop production on the dependent variable. Has a simultaneous influence between the independent variable and the dependent variable.